A Case of Traumatic Thoracic Outlet Syndrome - Lee, Tae Yeon (Korean Society for Thoracic and Cardiovascular Surgery, 2012)
Thoracic outlet syndrome (TOS) due to thoracic trauma is a rare disorder. Surgical treatment of TOS is especially rare. We report here a case of traumatic TOS caused by right 1st rib and clavicular fracture after a traffic accident. The patient underwent first rib resection and open reduction with fixation of the clavicle through axillary and supraclavicular incisions.